Health Behavior Education to Prevent Coronavirus Disease-19 in Orphanages: Roleplay Strategies - Kusumo, Mahendro Prasetyo (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND:There is currently a considerable international debate around school closings and children's role in transmitting SARS-CoV-2. AIM: This study wants to develop health education to increase knowledge and behavior of clean living in orphanages during the COVID-19 pandemic. METHOD: The design used was a quasi-experimental one-group pre-post-test design. The study was conducted at an orphanage located in Yogyakarta from October to December 2020. The sample size in this study was 171 orphanage with total sampling technique. The data collection technique used a questionnaire. Data were analyzed using paired-sample t-test. All children at the orphanage as respondents adjusted for inclusion criteria. The roleplay method through cartoon art performances was to convey the material. The questionnaire was used to assess the knowledge and practice of healthy living habits during the COVID-19 pandemic. RESULTS: The resulting data were analyzed using paired-sample t-test. There were differences in children's behavior before and after health education (p <0.005). The selection of educational methods was the primary key to success in increasing knowledge and healthy living behavior. The roleplay method using cartoon characters could convey health messages. Before playing the role, the researchers compiled scenarios and story transcripts used for health education. The atmosphere was relaxed and fun to increase children's motivation to get involved when delivering the material. CONCLUSION: The roleplay method through cartoon art performances effectively changed knowledge and behavior in healthy living during the COVID-19 pandemic. The story selection performed was the key to this method's success.